DEVELOPMENT OF TEACHING MATERIALS BASED ON THE RADEC MODEL TO IMPROVE THE HOTS OF GRADE V ELEMENTARY SCHOOL STUDENTS - Hasanatul Fitri; Yanti Fitria; Solfema; Elfia Sukma (Jurnal Cakrawala Pendas, 2023)
Challenges and changes in the 21st century require students to have 4C skills (Critical Thinking, Collaboration, Communication, and Creativity). These 4C skills are closely related to HOTS or higher-order thinking skills. Familiarizing students with HOTS skills in making decisions will be able to act quickly and efficiently compared to students who are less trained in HOTS thinking. These HOTS skills should be loaded into RADEC-based teaching materials. However, its application is still not optimal at the SD level. This study aimed to develop teaching materials based on the RADEC model (Read, Answer, Discuss, Explain and Create) to improve the good high-order thinking skills of fifth-grade elementary school students. The model used in this development research is the 4-D development model. It is a model that defines, designs, develop, and distributes information. Sixty-one fifth-grade students from SDN 35 Payakumbuh, SDN 13 Payakumbuh and SDN 07 Payakumbuh participated in this study. The products developed are tested for validity using validation sheets from material experts, linguists, and media experts. This validation sheet is used to determine the validity of their answers. Material expert validation scored 94% in the "very valid" category. For linguists, it was 95% in the "very valid" category, and media experts got 93% in the "very valid" category. This proves that RADEC Model-Based Teaching Materials To Increase Student HOTS Class V SD should properly be used as teaching materials in elementary schools. Tantangan dan perubahan pada abad ke 21 ini mengaharuskan siswa memiliki keterampilan 4C (Critical Thinking, Collaboration, Communication, dan Creativity). Keterampilan 4C ini sangat erat kaitannya dengan HOTS atau kemampuan berfikir tingkat tinggi. Membiasakan siswa untuk memiliki keterampilan HOTS dalam mengambil keputusan maka akan dapat bertindak cepat dan efisiensi jika dibandingkan siswa yang kurang dilatih dalam berpikir secara HOTS. Keterampilan HOTS ini harusnya dapat dimuat kedalam bahan ajar berbasis RADEC. Namun, penerapannya masih belum optimal pada jenjang SD. Tujuan penelitian ini adalah untuk mengembangkan bahan ajar berbasis model RADEC (Read,Answer,Disscuss,Explain and Create) untuk meningkatkan kemampuan berpikir tingkat tinggi siswa siswa kelas V sekolah dasar yang valid. Model yang digunakan dalam penelitian pengembangan ini adalah model pengembangan 4-D. Ini adalah model yang mendefinisikan, merancang, mengembangkan, dan mendistribusikan informasi. Sebanyak 61 siswa kelas V dari SDN 35 Payakumbuh, SDN 13 Payakumbuh dan SDN 07 Payakumbuh berpartisipasi dalam penelitian ini. Produk yang dikembangkan diuji validitasnya dengan menggunakan lembar validasi ahli materi, ahli bahasa dan ahli media. Lembar validasi ini digunakan untuk menentukan validitas jawaban mereka. Validasi ahli materi mendapat skor 94% kategori “sangat valid”, dari ahli bahasa adalah 95% kategori “sangat valid” dan ahli media mendapat skor 93% kategori “sangat valid”, Hal ini membuktikan bahwa Bahan Ajar Berbasis Model RADEC Untuk Meningkatkan HOTS Siswa Kelas V SD sudah selayaknya digunakan sebagai bahan ajar di sekolah dasar.